Constructing Snare Drum Handbook for Fifth Grade at Gu Jun Xian Chinese Culture Media Music Studio - Peng, Wu; Srisombut, Rujee (Asia Pacific Journal of Religions and Cultures, 2024)
The research objective was 1. to study snare drums from three key informants， and 2. to construct a snare drum handbook for teaching fifth-grade students. The research methodology was qualitative research. The research tools were the IOC interview form and evaluate handbook form. Key informants are three snare drum teachers at Guangdong and Xiamen. Study snare drum techniques from three key informants， and after that, construct the snare drum handbook and, in the end, the evaluation handbook for key informants. The snare drum is a versatile and expressive percussion instrument due to its sensitivity and responsiveness. It can use different drumsticks to make different sounds, and it has different gestures to strike, which is more attractive to students to learn. The snare drum can be learned faster and easier. Study the rudiments of snare drum teaching, construct a snare drum handbook, and explain the characteristics and practice methods of different rudiments of snare drum. The handbook contains 9 chapters, 13 knowledge points, and 32 etudes of different lengths. This handbook gives explanations and exercises from the simplest rhythm knowledge to advanced stroke so that students can learn every rudiment step by step and enhance students' interest in learning. After the handbook was completed. Three key informants checked its quality and the result is 0.77.